Parameters that affect the flexible structural number in AASHTO method - Kulo?lu, Necati; Erkmen, Reyhan (My University, 1996)
In this paper, the equation used for dimensining of highway parameters by AASHTO method and the effects of parameters in volued in the equation on the structural number is investigated in two parts. In part one, the relations of parameters with the structural number is considered. In part two, effects of errors in parameters in the structural number are studied. Results show that modulus of flexibilite of the subgrade soil is the most impoptant parameter to be considered.
AASHTO metodunda esnek üstyapi sayisina etki eden parametreler
Keywords: AASHTO; Flexible Pavement; Parameters; Pavement Design